Pembinaan kapasitas aparatur desa dalam pengelolaan administrasi desa di Kabupaten Bolaang Mongondow - Abdul R Dilapanga; Z.H Zingal (Seminar Nasional Pengabdian Kepada Masyarakat, 2014)
Village is a legal community unit that has a regional boundary that is authorized to regulate and administer government affairs, the interests of the local community based on community initiatives, the right of origin or traditional rights, which are grew, valid, and still recognized by the community in the government system of Indonesia. For the sake of the effectiveness of the village governance administration, the village government needs to be supported by the lawful village administration. Village administration is very important in managing village activities. The lawful and correct management of village administration is determined by the ability of the village apparatus. Limited resources of the village apparatus will affect the management of village administration. The purpose of this coaching program is to increase the capacity (ability) in the form of knowledge, understanding of government officials in the village administration in implementing the village administration model. In order to achieve these objectives, this coaching program provide a counseling session, mentoring and training to village officials. This activity is conducted for three months, which covers the preparation, implementation, strengthening program and evaluation stages. The results from the evaluation stage indicate that there is a change in the capacity of partner village officials in the management of village administration. The village apparatus highly appreciates and follows theguidance and strengthening of the program through practice using a module contains thirty-two village administration models.